Program Pengembangan Usaha Produk Olahan Jagung Dan Pemasaran Online Untuk Peningkatan Ekonomi Masyarakat Desa Tlangoh - Deni Tri Laksono; Dian Neipa Purnamasari; Yudi Andika Safittro; Moh. Iqbal Ramadlan. A; Monika Faswia Fahmi; Dedi Tri Laksono (Jurnal Insan Pengabdian Indonesia, 2023)
Corn (Zea mays L.) is a monoecious plant with separate male and female flowers on a single plant. Apart from being a staple food, corn is used for livestock feed and export purposes. Despite the development of corn production technologies by research institutions, they have not been widely adopted by farmers due to traditional drying methods and quick post-harvest sales. Enhancing corn's competitiveness requires efforts to improve economic efficiency, quality, and productivity through technology adoption, from cultivation to post-harvest marketing. In the era of Industry 4.0, rapid technological advancements and digital marketing are reshaping product marketing strategies. In Tlangoh Village, sales are still conventional. Hence, the aim of this activity is to provide training and mentoring in digital marketing to enhance the effective marketing of corn products in Tlangoh Village, expanding market access and optimizing product value.